Evidence of Greenwashing in Talent Attraction: Can Job Seekers Successfully Detect Deceptive Job Advertisements? - Lars Speckemeier; Dimitrios Tsivrikos (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This research explores the effects of greenwashing on employer branding and job pursuits. Through the lens of signaling theory, we specifically examine the interaction of deceptive green marketing and perceived green organization image, aiming to highlight the conditions under which talents disregard the authenticity of job advertisements. Across four field experiments, using a total of 941 actual job seekers, we found that genuine green marketing leads to the highest attraction scores. However, when the perceived green identity of a company is low, green marketing can lead to an even lower number of applications than no green marketing. Thus, green marketing does not increase job attraction per se. It is rather a function of identity and ad campaign design. We also found that among participants with high environmental attitudes, the negative effects of greenwashing are amplified, resulting in even lower job pursuit intentions. On the contrary, job seekers with high person-organization fit appear to be unaffected by deceptive marketing. We are among the first studies to incorporate the notion of inauthentic green employer branding in job advertising and, in doing so, provide a new theoretical viewpoint of how talent’s perceptions of employers are built and modified. Our results aim to show to employers that providing misleading information harms job attraction and to provide insights on how to reduce greenwashing practices in the recruitment domain.